KARAKTERISTIK SIMPLISIA DAN SKRINING FITOKIMIA SENYAWA ALKALOID, FLAVONOID, TANIN, DAN SAPONIN EKSTRAK ETANOL DAUN COCOR BEBEK (Kalanchoe pinnata (Lam) Pers.) - Purwanti, Ratih; Nur Kholifah, Diah (Jurnal Permata Indonesia, 2025)
The Kalanchoe pinnata (Lam.) Pers. plant, commonly known as "cocor bebek" in Indonesia, is known for its vegetative reproduction through leaf buds. In addition to this unique reproductive method, the plant possesses various pharmacological properties, including antibacterial, antifungal, antiviral, antioxidant, and antidepressant effects. The content of active compounds in this plant can be influenced by environmental factors such as growing location, climate, and geographical conditions. Therefore, it is important to conduct a characterization of the simplicia and a phytochemical screening to identify the active compounds present. The objective of this study was to determine the characteristics of the simplicia and the results of phytochemical screening for alkaloids, flavonoids, tannins, and saponins in the ethanol extract of Kalanchoe pinnata leaves. This research is a descriptive study using a single variable, namely the characterization of simplicia and phytochemical screening. The macroscopic characterization results of the simplicia showed that the leaves of Kalanchoe pinnata conformed to their typical morphological characteristics. The moisture content, determined by drying loss, was found to be 23.50% ± 4.15 on average. The average ethanol-soluble extractive content was 32.33% ± 3.32, while the water-soluble extractive content was 22.60% ± 12.09. The results of the phytochemical screening indicated that the ethanol extract of Kalanchoe pinnata leaves tested positive for alkaloids, flavonoids, saponins, and tannins. Keywords: cocor bebek, phytochemical screening, simplicia